Mobile eateries SMEs: occidentals & Malaysia chronicles/ Mohd Remie Mohd Johan, Md. Azalanshah Md. Syed and Hamedi Mohd Adnan - Mohd Johan, Mohd Remie; Md. Syed, Md. Azalanshah; Mohd Adnan, Hamedi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Malaysia might be described as a gourmet paradise, given the distinctiveness of its food, beverages, and food cultures. This article aims to explore the various literature on mobile eateries development in the global and Malaysian context. Thus, we investigate small and medium enterprise and mobile eateries' evolution, roles, and contributions in gastronomic tourism. Gastronomy encompasses an appreciation for diverse social, cultural, and historical components and literature, philosophy, economics, and religion, which revolve around food. We examined online and offline secondary sources of academic and non-academic reports, articles, images, and illustrations. The comparison was made on mobile eateries concept, growth, and development in global and Malaysia context. This article found the various ideas of mobile eateries, including hawkers, street food vendors, and food trucks, that significantly contributed to the holistic gastronomy concept in the global and Malaysian context as a food paradise. Mobile eateries in Malaysia also continue to grow and have significant contributions to the national socio-economic growth in Malaysia.